Phenolic and Sensorial Evolution during Bottle Ageing of South African Shiraz Wines with Different Initial Phenolic Profiles - G. Garrido-Bañuelos, G.; Buica, A.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2020)
The aim of this research was to evaluate the colour and phenolic evolution of Shiraz red wines made from the same vineyard, but with different initial phenolic profiles. Several vineyard-related variables were initially evaluated in a first vintage (2014), but grape ripeness was shown to be the most determining factor on most of the phenolics and the taste and mouthfeel of the wines. In the second vintage (2015), wines made from four different ripeness levels were aged up to 18 months and periodically analysed during this period. The results show how Shiraz wines with different initial phenolic profiles might develop differently over time during bottle ageing. In the second vintage, some of the colour and phenolic parameters of the wines were similar after completing the alcoholic fermentation (AF). However, these small differences between the wines became more noticeable over time, especially when comparing the wines made from the highest sugar level with the rest. These differences were especially noticeable in the polymeric fraction (polymeric phenols and polymeric pigments), with a larger number of polymeric forms found in the wines made from the ripest berries, and subsequently a larger formation of polymeric pigments. Differences in the wines’ phenolic composition, and the differences in the alcohol content of the wines, also influenced the taste and mouthfeel evaluation of the wines, and these were maintained over time.